Thermal and mechanical properties of gypsum plaster mixed with expanded polystyrene and tragacanth - Bicer, Ayse; Kar, Filiz (Elsevier, 2017)
In this paper, the employability of waste Expanded Polystyrene Foam (EPS) as filling material in the plaster with resin added gypsum by means of revaluation has been examined. After waste EPS is collected as packaging material and disintegration according to 0-3 mm particle diameters and mixed with the gypsum of percentages; 20%, 40%, 60% and 80%. Tragacanth is added to each of this binder at 0.5%, 1% and 1.5% of the weight of the mixture in order to create artificial pores on gypsum block. The samples of 16 different combinations are produces. They are subjected to some tests to find out their properties. It is found that; the thermal conductivity, the compression and tensile strength decreases with increasing amount of EPS and tragacanth in the mixture. Produced samples must not be used in external plaster which is subjected to water against the danger of freezing as the water absorption rate was found higher than 30%. With this study, it is recommended that the samples should be used as internal plaster, insulation plaster and decoration material due to their canal opening and paint sustention features. If this plaster and decoration material is used, (i) the waste EPS will be evaluated and environmental pollution will be prevented, (ii) building heating and cooling energy will be saved. (C) 2017 The Authors. Published by Elsevier Ltd.
Keywords: Expanded polystyrene; Tragacanth; Gypsum; Insulation plaster